Strategy in Building Skills Entrepreneurial Senior High School Students in Surabaya - Setiyono, Rizal; Sarmini, Sarmini; Jacky, M (The Indonesian Journal of Social Studies, 2021)
Purpose of this research is to make the right strategy to build entrepreneurial skills at SMA Muhammadiyah 9 Surabaya. This study uses a qualitative method with a case study approach. Data were collected through teachers related to the school's entrepreneurship program and students who were active in entrepreneurial activities. Entrepreneurial activities at SMA Muhammadiyah are analyzed using constructivist learning theory in which students will be grouped with the group. The exchange of ideas, thoughts, and experiences in entrepreneurship will help in developing students' entrepreneurial skills. The existence of field trsocial studies supports students' entrepreneurial skills because students are directly dealing with varied consumers. No less important is a marketing strategy through effective social media in this all-digital era. Growing social capital in terms of beliefs, networks, norms and values. Can help in terms of entrepreneurship of students. The results can build students' entrepreneurial skills with these three strategies. Evidenced by the results of observations and student work reports. students can be more dexterous in selling their products and can make good and correct reports.